2013
DOI: 10.1111/pbr.12118
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of genetic diversity between wild and cultivated barley using gSSR and ESTSSR markers

Abstract: Barley is an economically important cereal crop especially for feed and malt production, but its value as food is increasing due to various health benefits. Wild barley is the progenitor of modern day barley cultivars possessing a rich source of genetic variation for various biotic and abiotic stresses. Species‐specific molecular markers have great potential for efficient introgression of these important traits from wild to cultivated barley. In the present study, 140 microsatellite markers were screened to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 33 publications
7
25
1
Order By: Relevance
“…On average, the SSR mapped markers amplified 4 alleles per SSR, with a range from 2 to 6 alleles per SSR, which was comparable to the value (4 in average) of the 33 SSR which is similar to the study of [16] on Iranian barley landraces. Our study up to some similarity are similar to the previously published reports of [21] which the conducted their study on Indian accessions of barley and lower than the ones published by others [11][12][13][14]17] Bmac0181, Bmag0120, Bmag0125, Bmag0603, Bmac0156, Bmag0900 and Bmag0872, were highly polymorphic, each producing 6 to 5 alleles. Other fifteen SSR primer pairs, namely, Bmac0030, Bmac0067, Bmac0093, Bmac0129, Bmag0173, Bmac0096, Bmag0013, Bmag0606, Bmag0125, Bmag0720, EBmac0501, EBmac0764, EBmac0603, Bmag0812 and Bmag0829 was moderately polymorphic, each producing four to three alleles.…”
Section: Discussionsupporting
confidence: 91%
“…On average, the SSR mapped markers amplified 4 alleles per SSR, with a range from 2 to 6 alleles per SSR, which was comparable to the value (4 in average) of the 33 SSR which is similar to the study of [16] on Iranian barley landraces. Our study up to some similarity are similar to the previously published reports of [21] which the conducted their study on Indian accessions of barley and lower than the ones published by others [11][12][13][14]17] Bmac0181, Bmag0120, Bmag0125, Bmag0603, Bmac0156, Bmag0900 and Bmag0872, were highly polymorphic, each producing 6 to 5 alleles. Other fifteen SSR primer pairs, namely, Bmac0030, Bmac0067, Bmac0093, Bmac0129, Bmag0173, Bmac0096, Bmag0013, Bmag0606, Bmag0125, Bmag0720, EBmac0501, EBmac0764, EBmac0603, Bmag0812 and Bmag0829 was moderately polymorphic, each producing four to three alleles.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the root architecture takes major role in plant adaptation to drought (Chloupek et al, 2010; Wasson et al, 2012; Barati et al, 2015). Although, numerous GWAS studies have been made on barley diversity analysis by Nandha and Singh (2014) and Russell et al (2014), but genetic dissection of root traits remained fragmented due to difficulty for its phenotypic evaluations. To our knowledge, the current work presents the first study of its kind that utilized world-wide germplasm of barley to investigate the essential root and related shoot trait variations using a high resolution SNP map through GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, wild barley accessions showed higher values for Rdw, Til, and RS as compared to cultivated varieties. Nandha and Singh (2014) studied 27 wild accessions originating from the Middle East as well as 20 cultivars and found the presence of vital exotic alleles in determining root trait variation. Tyagi et al (2011) reported significant environmental adaptation among the wild accessions from the Fertile Crescent.…”
Section: Discussionmentioning
confidence: 99%
“…The PCoA and cluster analysis distinguished these cultivars into different groups (Gong et al 2011). The first principal coordinate accounted for 18.4% of the total variation, clearly separating the wild genotypes from the cultivated ones, and the second principal coordinate accounted for 10.4% of the total variation and consisted of all cultivated genotypes (Nandha and Singh 2014). PCoA based on ISSR data clearly differentiated Ethiopian faba bean varieties into three distinct groups.…”
Section: Srap Analysismentioning
confidence: 90%